Advances in Human Factors in Robots and Unmanned Systems Proceedings of the AHFE 2016 International Conference on Human Factors in Robots and Unmanned Systems, July 27-31, 2016, Walt Disney World®, Florida, USA - Savage-Knepshield, Pamela; Chen, Jessie; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book focuses on the importance of human factors in the development of reliable and safe unmanned systems. It discusses current challenges such as how to improve perceptual and cognitive abilities of robots, develop suitable synthetic vision systems, cope with degraded reliability of unmanned systems, predict robotic behavior in case of a loss of communication, the vision for future soldier-robot teams, human-agent teaming, real-world implications for human-robot interaction, and approaches to standardize both display and control of technologies across unmanned systems. Based on the AHFE 2016 International Conference on Human Factors in Robots and Unmanned Systems, held on July 27-31, 2016, in Walt Disney World®, Florida, USA, this book is expected to foster new discussion and stimulate new ideas towards the development of more reliable, safer, and functional devices for carrying out automated and concurrent tasks.
A Vision for Future Soldier-Robot Teams -- Confronting Human Factors Challenges -- Human-Agent Teaming -- From Theory to Application: UAV and Human-Robot Collaboration -- Supporting Sensor and UAV Users -- An Exploration of Real-World Implications for Human-Robot Interaction -- Optimizing Human-Systems Performance through System Design.
Keywords: Computational intelligence; Control engineering; Robotics; Automation; Psychology, Experimental; User interfaces (Computer systems).; Human-computer interaction; Computational Intelligence; Control, Robotics, Automation; Experimental Psychology; User Interfaces and Human Computer Interaction